BIOM-03. INVASIVE HISTOPATHOLOGY DRIVES POOR OUTCOMES IN SURGICALLY RESECTED BRAIN METASTASES. (9th November 2020) - Dankner, Matthew; Caron, Maxime; Al-Saadi, Tariq; Yu, WenQing; Ouellet, Veronique; Ezzeddine, Rima; Annis, Matthew G; Le, Phuong Uyen; Nadaf, Javad; Neubarth, Noah S; Savage, Paul; Zuo, Dongmei; et al.
Abstract: BACKGROUND: Surgery as a single modality for the treatment of brain metastases (BrM) results in local recurrence (LR) in 60% of patients. These failure rates are reduced by half with post-operative radiotherapy. The non-invasive nature of BrM has led to the assumption that local recurrence is caused by spillage of cancer cells into the surgical cavity at the time of surgery. We present evidence suggesting that invasion of metastatic cancer cells into the adjacent brain is present in the majority of BrM and is associated with LR, leptomeningeal metastasis (LM), and overall survival (OS). METHODS: We assessed the histopathological growth pattern (HGP) of 164 surgically resected BrM. HGP was correlated with LR, LM and OS. Single-cell transcriptomics (scRNAseq) was performed on 15, 615 cells from metastasis center (MC) and surrounding brain (SB) adjacent to the tumor. N=30 orthotopic patient-derived xenograft models (OPDX) were established from BrM. RESULTS: 56/164 (34%) BrM specimens showed a minimally invasive (MI) HGP between the tumor and adjacent brain while 108/164 (66%) showed significant invasion of tumor lobules or single-cells into the brain (HI-HGP). HI-HGP was associated with LR, LM and shortened OS in BrM patients. scRNAseq identified abundant cancer cells in SB that overexpressed pathways and genes involved in cell survival and stress adaptation compared to matched cancer cells in MC. Validation of these targets with immunohistochemistry in patient and OPDX tissues revealed cold-inducible RNA binding protein (CIRBP) overexpression in HI-HGP patient and OPDX BrM. Modulation of CIRBP expression in OPDX and cell line models of HI-HGP BrM delayed BrM progression and extended OS. CONCLUSION: HI-HGP is a poor prognostic indicator in patients with surgically resected BrM, establishing HGP as an important prognostic factor that should be considered by clinicians treating BrM patients. We identify CIRBP as a functional mediator of this process.